PENGARUH PERSEPSI HARGA DAN PERCEIVED VALUE TERHADAP KEPERCAYAAN KONSUMEN: STUDI PADA MAHASISWA MANAJEMEN FEB UNIVERSITAS HALU OLEO KENDARI - Dzulfikri Azis Muthalib (Jurnal Multidisipliner Bharasumba, 2026)
This study aims to analyze the effect of price perception and perceived value on consumer trust among students of the Management Study Program, Faculty of Economics and Business, Universitas Halu Oleo, who actively engage in online shopping. This research employs a quantitative approach with a causal research design. Data were collected through an online questionnaire distributed to 90 respondents selected using purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that price perception has a positive and significant effect on consumer trust. In addition, perceived value also has a positive and significant effect on consumer trust, with a more dominant influence compared to price perception. Simultaneously, price perception and perceived value explain a substantial proportion of the variance in students’ consumer trust. These findings suggest that students evaluate e-commerce transactions holistically by considering price fairness as well as the perceived functional, emotional, and social value.